Logic, Rationality, and Interaction: 6th International Workshop, LORI 2017, Sapporo, Japan, September 11-14, 2017, Proceedings - Baltag, Alexandru; Seligman, Jeremy; 山田, 友幸 (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2017)
This LNCS volume  is part of FoLLI book serie and contains the papers presented at the 6th International Workshop on Logic, Rationality and Interaction/ (LORI-VI), held in September 2017 in Sapporo, Japan.  The focus of the workshop is on following topics: Agency, Argumentation and Agreement, Belief Revision and Belief Merging, Belief Representation, Cooperation, Decision making and Planning, Natural Language, Philosophy and Philosophical Logic,  and Strategic Reasoning.